MODEL PENANGANAN ANAK BERKESULITAN BELAJAR SPESIFIK KARENA FAKTOR DISFUNGSI MINIMAL OTAK (DMO) DI SEKOLAH DASAR - . MUNAWIR (DIMENSI PENDIDIKAN, 2005)
This study is porposed to : (1) encompass and identify the students od elementary school who are expected to have spesific learning difficulty because of Brain Minimal Disfunction, (2) understand of the teacher action model and its intervention effect toward the increasing of children learning performance. The research was done in Gamping, Sleman in year 2000. Stage 1 : 10 of 40 elementary school in Gamping, Sleman were chosen. Stage 2 : Student of second and third grade were selected as research subject. The methods of data collection are observation, interview, and demostration. The research is done by research team and the class teacher. The result of this study?é?á and the conclusion show that from 523 students of the second and third grade of 10 elementary scoool, 45 students (8,60%) have mathematic spesific learning difficulties, 36 students (6,88%) have writing difficulties. A class teacher gives remedial teaching and special guide will help students to over-come learning difficulties with special class model, source room model and regular class model. Keyword : Treatment of children with specific learning difficulty